Use of ward closure to control outbreaks among hospitalized patients in acute care settings: a systematic review. Issue 1 (December 2015) - Wong, Holly; Eso, Katherine; Ip, Ada; Jones, Jessica; Kwon, Yoojin; Powelson, Susan; de Grood, Jill; Geransar, Rose; Santana, Maria; Joffe, A.; Taylor, Geoffrey; Missaghi, Bayan; et al.
Abstract Background Though often used to control outbreaks, the efficacy of ward closure is unclear. This systematic review sought to identify studies defining and describing ward closure in outbreak control and to determine impact of ward closure as an intervention on outbreak containment. Methods We searched these databases with no language restrictions: MEDLINE, 1946 to 7 July 2014; EMBASE, 1974 to 7 July 2014; CINAHL, 1937 to 8 July 2014; and Cochrane Database of Systematic Reviews, 2005 to May 2014. We also searched the following: IndMED; LILACS; reference lists from retrieved articles; conference proceedings; and websites of the CDCP, the ICID, and the WHO. We included studies of patients hospitalized in acute care facilities; used ward closure as a control measure; used other control measures; and discussed control of the outbreak(s) under investigation. A component approach was used to assess study quality. Results We included 97 English and non-English observational studies. None included a controlled comparison between ward closure and other interventions. We found that ward closure was often used as part of a bundle of interventions but could not determine its direct impact separate from all the other interventions whether used in parallel or in sequence with other interventions. We also found no universal definition of ward closure which was widely accepted. Conclusions With no published controlled studies identified, ward closure for control of outbreaks remains an intervention that is not evidence based and healthcare personnel will need to continue to balance the competing risks associated with its use, taking into consideration the nature of the outbreak, the type of pathogen and its virulence, mode of transmission, and the setting in which it occurs. Our review has identified a major research gap in this area.